Evaluation of electrocardiographic parameters for early diagnosis of autonomic dysfunction in children and adolescents with type‐1 diabetes mellitus. Issue 5 (17th September 2014) - Uysal, Fahrettin; Ozboyaci, Evren; Bostan, Ozlem; Saglam, Halil; Semizel, Evren; Cil, Ergun
Abstract Background The aim of this study was to identify the sensitivity of electrocardiogram (ECG) in early diagnosis of cardiac autonomic function disorder in children with type 1 diabetes mellitus. Methods A total of 150 children and adolescents with type 1 diabetes mellitus were enrolled between June 2009 and June 2010, as well as 100 age‐ and sex‐matched healthy control children. Twelve‐lead ECG was done in all cases and heart rate, QT and QTc interval, dispersion of P wave (Pd), and of QT (QTd) and QTc interval (QTcd) were measured. The clinical and demographic features such as age, gender, duration of follow up and level of HbA1c and fasting glucose were obtained and the effects of these parameters on ECG measurements were investigated. Results The mean age of the patients and controls was 11.61 ± 3.72 years and 10.92 ± 3.2 years, respectively. QT and QTc interval and QTcd interval were significantly higher in diabetic children compared to healthy controls but these ECG findings were not associated with the duration of diabetes or glycemic state. Pd was significantly higher in the diabetic patients with HbA1c >7.5% compared to control, and this was also found in patients that were followed up >1 year. Conclusions Cardiac autonomic function disorder, which is one of the most important causes of morbidity and mortality, may emerge in the course of type 1 diabetes mellitus. It can be diagnosed on ECG even when the patients are asymptomatic.